DNA ploidy analysis on lymphoma using archival paraffin tissue section - Norizan Mohd Annuar; Gregory A.R.A (penerbit ukm, 2004)
In this retrospective study of lymphomas, DNA content and proliferative index of 37 histopathologically confirmed cases of lymphoma consisting of 29 male and 8 female were measured using a flowcytometer. This was carried out using paraffin embedded tissues of cases diagnosed in the Department of Pathology, Hospital Kuala Lumpur, over a period of 1990 to 1995. Among them, 24 were diagnosed to be non-Hodgkin’s lymphomas (NHL) while 13 were diagnosed as Hodgkin’s disease (HD). Lymph nodes showing reactive changes and tonsils removed for chronic inflammation were used as control. Of all the cases studied for NHL (B cell = 70.8%, T cell = 8.3% and unclassified cases = 20.9%), 12.5% were near diploid (DNA index, DI = 1.0 - 1.10), 66.7% were hyperdiploid (DI = 1.10 - 1.85) and 20.8% were hypodiploid (DI < 1.0). Majority of the hyperdiploid cases were B cell type of NHL. In HD (mixed cellularity = 1, nodular sclerosing = 5, lymphocyte predominant = 1 and unclassified = 6) 30.8% were near diploid, 46.1% were hyperdiploid and 23.1% were hypodiploid. The significant finding of this study was that the majority of the NHL and HD showed a high proliferative index.